Evidence of Elevational Speciation in Kerteszia cruzii (Diptera: Culicidae) in the Ribeira Valley, São Paulo, Brazil - Demari-Silva, Bruna; Laporta, Gabriel Zorello; de Oliveira, Tatiane Marques Porangaba; Sallum, Maria Anice Mureb (Frontiers in Ecology and Evolution, 2021)
Kerteszia cruzii (former Anopheles (Kerteszia) cruzii) is a bromeliad mosquito widespread in the Brazilian Atlantic rainforest. In South-eastern Brazil, it plays an important role in malaria transmission because it was infected with at least four Plasmodium species. There is robust evidence that Ke. cruzii is a species complex. We used single nucleotide polymorphisms (SNPs) from a nextRAD sequence (nextera-tagmented, reductively amplified DNA) to investigate the genetic structure of Ke. cruzii in the Ribeira Valley, South-eastern Brazil. Furthermore, we verified whether the genetic structure was associated with forest cover, elevation, slope, and vegetation physiognomy. Our results showed two distinct lineages in the studied region: elevation and isolation by distance. The first lineage included samples from coastal localities and the second comprised specimens from inland or mountain sites. At one sampling locality (Esteiro do Morro in Cananéia municipality), both lineages are sympatric. These results are in accordance with previously published data that showed elevated stratification in Ke. cruzii. However, Fst values did not indicate the existence of cryptic or sister species in Ke. cruzii in this region, we concluded that elevational speciation probably occurs, and we hypothesized that differences in population structure found might be associated with the distribution of bromeliad species.